Produktivitas dan Kualitas Buah Manggis (Garcinia manggostana L.) di Purwakarta - Eko Setiawan; Roedhy Poerwanto (Universitas Trunojoyo Madura, 2008)
Indonesian mangosteen is a prospective product to be exported to Europe, Middle East, East Asia such as Taiwan, Hong Kong, Singapore, and Japan. Indonesian exported commodities increase significantly from year to year, but the increasing volume was not followed by an improvement in the production and quality of the fruit. Mangosteen has symmetrical branches that form a dense canopy that protect sun radiation intensity to penetrate, and it keeps the radiation intensity remain below normal of its need. Most of the harvested mangosteen plants owned by the community were not managed properly. It causes the production and quality of the fruit below standard. The research aims at (1) knowing the position of the buds and fruit at various branches within the canopy, (2) collecting information about the distribution of production and quality of the fruit. The research was done from September 2003 to May 2004 at the center of mangosteen fruit production in west Java, i.e. Sub-district of Wanayasa, District of Purwakarta. The research was done on randomized complete block design which consists of nine sectors of branches with seven replications. The nine sectors are sector 1 (inner bottom canopy), sector 2 (center bottom canopy), sector 3 (outer bottom canopy), sector 4 (inner middle canopy), sector 5 (center middle canopy), sector 6 (outer middle canopy), sector 7 (inner top canopy), sector 8 (center top canopy), sector 9 (outer top canopy). The result of research showed that the most frequent emergence of bud and fruit in Wanayasa was found in sector 3 (outer bottom canopy), sector 4 (inner middle canopy) and sector 5 (center middle canopy). Sector 6 (outer middle canopy), produce more vegetative branches. Dense canopy structure of upper branches has protect inner and bottom canopy from light availability. On average, the quality of the fruit is below standard. In Wanayasa, only 0.6-0.7% of the fruit meets the quality of Super SNI which produced especially on sector 4 and sector 5. At average, distribution of quality I was about 8.8-18.2%; distribution of quality II was about 7.7-36.4%; and more than 50% of the production does not meet the quality standards.